Synthesis, Characterization and Antimicrobial Activity of a Tridentate Hydrazide-hydrazone Ligand Derived from 2-Pyridinecarboxaldehyde and 4-Hydroxybenzohydrazide and Its Co(II) and Zn(II) Complexes - Jabbi, Abubakar Muhammad; Aliyu, Habu Nuhu (FUDMA Journal of Sciences, 2026)
A hydrazide-hydrazone ligand was synthesized through the condensation of 2-pyridinecarboxaldehyde and 4-hydroxybenzohydrazide. Its corresponding Co(II) and Zn(II) complexes were prepared and characterized bysolubility, melting point and decomposition temperature, elemental analysis, molar conductance, magnetic susceptibility, FTIR, and UV-Vis spectroscopic techniques. Analytical and spectroscopic data confirmed the formation of neutral complexes [Co(L)Cl2(H2O)].H2O and [Zn(L)Cl2].H2O. The IR spectral data of the ligand showed a band at 1648cm-1 which were assigned tohydrazide carbonylv(C=O) this same band was observed to shift  to lower frequencies 1635, 1633 cm-1, after complexation. Another band appeared at 1560 cm-1assigned to azomithene v(C=N) and the sameband was observed to shift  to higher frequencies 1600 cm-1 and 1611 cm-1in the complexes, suggesting coordination of the ligand with the respective metal(II) ions. Other peaks appeared at 608, 577;508, 551 cm-1 which are attributed to v(M-N) and v(M-O) respectively, showing that the ligand coordinated in a tridentate manner through hidrazide oxygen, azomethine nitrogen and pyridyl nitrogen. The magnetic moment 4.58 BM of Co(II) suggested its paramagnetic nature, while the value for the Zn(II) complex suggested its diamagnetic nature (0 BM). Molar conductance values 11.58 and 2.70Ω-1cm2mol-1 confirmed the neutral nature of both complexes. The result of the antimicrobial showed that the hydrazide-hydrazone ligand itself possessed inherent antifungal properties against Candida albicans, Tinea rub rum and Tinea pendisthat may be diminished rather than enhanced by metal coordination. This contrasted with the antibacterial results for tested bacteriaStaphylococcus aures, Eschirichia coli and Pseudomonas ariginosa where metal complexation generally improved the activity.
Keywords: Tridentatehydrazide-Hydrazone; Antimicrobial; Metal(II) Complexes